Insulin Resistance and Oxidative Stress: In Relation to Cognitive Function and Psychopathology in Drug-Naïve, First-Episode Drug-Free Schizophrenia - Tao, Qi; Miao, Yu; Li, Huihui; Yuan, Xiuxia; Huang, Xufeng; Wang, Yunpeng; Andreassen, Ole A.; Fan, Xiaoduo; Yang, Yongfeng; Song, Xueqin (Frontiers in Psychiatry, 2020)
Objective: The present study aimed to examine whether insulin resistance and oxidative stress are associated with cognitive impairment in first-episode drug-free schizophrenia (SZ) patients. Methods: Ninety first-episode SZ patients and 70 healthy controls were enrolled. Fasting insulin (FINS) and markers of oxidative stress [oxidized glutathione (GSSG), superoxide dismutase (SOD), nitric oxide (NO) and uric acid (UA) levels] were measured in serum before pharmacological treatment was initiated. Psychiatric symptoms and cognitive function were assessed with the Positive and Negative Syndrome Scale (PANSS) and MATRICS Consensus Cognitive Battery (MCCB), respectively. In addition, the homeostatic model assessment of insulin resistance (HOMA-IR) was also studied. Results: HOMA-IR and serum levels of GSSG and NO were significantly higher in SZ patients than in healthy controls (P < 0.001), while the serum levels of SOD were significantly lower than in healthy controls (P < 0.001). HOMA-IR, GSSG and NO levels were significantly correlated to the total cognitive function scores of the patient group (r = −0.345,−0.369,−0.444, respectively, P < 0.05). But these factors were not co-related to the cognitive functions in the healthy control group. And, levels of SOD, UA were not associated with the total cognitive function scores in both the patient and the healthy control groups. NO was positively correlated with general pathological and the total score in the PANSS, and was negatively correlated with six cognitive domains (r = −0.316 to −0.553, P < 0.05). Conclusions: The levels of insulin resistance and oxidative stress are elevated, and correlated with the severity of cognitive impairment in drug-naïve, first-episode SZ patients. Treatment approaches targeting on reducing insulin resistance and oxidative stress may improve cognitive function in SZ patients.